First experimental results with new ICRF antenna in EAST. (1st August 2022) - Zhang, X.J.; Yang, H.; Qin, C.M.; Yuan, S.; Zhao, Y.P.; Wang, Y.S.; Liu, L.N.; Mao, Y.Z.; Cheng, Y.; Gong, X.Z.; Xu, G.S.; Song, Y.T.; et al.
Abstract: A new ion cyclotron range of frequency (ICRF) antenna, instead of a B-port antenna, is installed at the N-port to improve the power coupling in the 2021 experimental advanced superconducting tokamak (EAST) experimental campaign. In all the experiments, a frequency of 37 MHz is used, corresponding to hydrogen minority heating of deuterium plasma at B 0 = 2.5 T. The maximum coupling resistance is up to 10 Ω, which is close to two times the resistance of the original two antennas in EAST. The plasma stored energy is increased by 30 kJ MW −1, and significant core ion and electron heating are observed. For long pulse operation, we have achieved 1.5 MW/41 s and 1.1 MW/61 s with the new antenna in the high poloidal beta plasma discharge. ICRF power up to 1.8 MW is routinely coupled to the plasma for pulse lengths up to 21 s.